2014
DOI: 10.1152/japplphysiol.00797.2013
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nitrate facilitates an acetazolamide-induced increase in cerebral blood flow during visual stimulation

Abstract: Aamand R, Ho YL, Dalsgaard T, Roepstorff A, Lund TE. Dietary nitrate facilitates an acetazolamide-induced increase in cerebral blood flow during visual stimulation. J Appl Physiol 116: 267-273, 2014. First published December 12, 2013 doi:10.1152/japplphysiol.00797.2013The carbonic anhydrase (CA) inhibitor acetazolamide (AZ) is used routinely to estimate cerebrovascular reserve capacity in patients, as it reliably increases cerebral blood flow (CBF). However, the mechanism by which AZ accomplishes this CBF inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Further, reduced NO bioavailability and signaling has been implicated in disrupted neurovascular coupling in which cerebrovascular blood flow is no longer matched to regional metabolic demand, thereby destabilizing neurons, synapses and neurotransmission [ 53 , 56 ]. Consistent with this idea, evidence of improved coupling of blood flow to visual stimuli with co-administration of nitrate and the carbonic anhydrase inhibitor acetazolamide has been shown in young men [ 57 ]. Lastly, in preclinical studies in mice, we have demonstrated that chronic low-grade inflammation, as indicated by elevated tissue expression of pro-inflammatory cytokines, is a major mechanism contributing to vascular and motor dysfunction with aging [ 58 , 59 ], and that sodium nitrite supplementation reverses age-related increases in vascular and skeletal muscle inflammation in these models [ 55 , 59 ].…”
Section: Discussionmentioning
confidence: 81%
“…Further, reduced NO bioavailability and signaling has been implicated in disrupted neurovascular coupling in which cerebrovascular blood flow is no longer matched to regional metabolic demand, thereby destabilizing neurons, synapses and neurotransmission [ 53 , 56 ]. Consistent with this idea, evidence of improved coupling of blood flow to visual stimuli with co-administration of nitrate and the carbonic anhydrase inhibitor acetazolamide has been shown in young men [ 57 ]. Lastly, in preclinical studies in mice, we have demonstrated that chronic low-grade inflammation, as indicated by elevated tissue expression of pro-inflammatory cytokines, is a major mechanism contributing to vascular and motor dysfunction with aging [ 58 , 59 ], and that sodium nitrite supplementation reverses age-related increases in vascular and skeletal muscle inflammation in these models [ 55 , 59 ].…”
Section: Discussionmentioning
confidence: 81%
“…In vitro studies have shown nitrite reducing effects of CA, and suggest a stimulatory effect of acetazolamide on NO generation, despite the inhibition of CO 2 hydration [ 13 , 14 ]. A recent clinical trial found a positive effect of nitrate intake on the increase in visually stimulated cerebral blood flow when injecting acetazolamide in healthy male subjects [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the former could theoretically provide a convenient way of exporting nitrite-derived NO from RBCs under hypoxic conditions, recent animal experimental results suggest that the majority of hypoxic vasodilatation is not mediated by Hbmediated nitrite reduction (Umbrello et al, 2014). The nitrite reductase activity of carbonic anhydrase appears to be linked to the coupling of cerebral blood flow and metabolic activity in response to visual stimulation (Aamand et al, 1985(Aamand et al, , 2009.…”
Section: Mechanisms Of Nitrite-mediated Vasodilatationmentioning
confidence: 99%